Cervical single open-door laminoplasty with or without local lateral mass screw fixation and fusion to treat cervical spinal cord injuries accompanied by segmental spinal canal stenosis - Yu, Zihao; Xie, Hongwei; Ouyang, Ziyu; Zhang, Hua (Frontiers in Surgery, 2023)
Study Design Retrospective. Objectives To investigate the efficacy of cervical single open-door laminoplasty with and without local lateral mass screw fixation and fusion as treatments for cervical spinal cord injuries accompanied by multisegmental spinal canal stenosis. Setting The Second Affiliated Hospital, School of Medicine, Zhejiang University. Methods Of all enrolled patients, 42 formed a stable group who underwent cervical single open-door laminoplasty alone and 14 formed an unstable group who underwent the procedure combined with lateral mass screw fixation and fusion. Neurological function was evaluated before surgery, at discharge, and at final follow-up using the American Spinal Cord Injury Association (ASIA) impairment scale and the Japanese Orthopedic Association (JOA) score. Results ASIA scores reflected improved neurological function in 52.5% of the stable group (15 with grade-D and 4 with grade-A injuries did not improve) and 45.5% of the unstable group (3 with grade-D and 3 with grade-A injuries did not improve). Postoperative JOA scores reflected 19.1% ± 21.6% improvement in the stable group and 18.6% ± 18.4% improvement in the unstable group (P > 0.05). Final follow-up JOA scores reflected 49.2% ± 31.7% improvement in the stable group and 47.1% ± 39.2% improvement in the unstable group (P > 0.05). Conclusions Laminoplasty combined with local fusion aided the treatment of unstable cervical spinal cord injuries and spinal stenosis. Such stenosis is the main pathological factor causing multiple spinal cord compressions in patients with cervical spinal cord injuries.